Converse: Brand Image & Product Quality Effect through Customer Satisfaction toward Repurchase Intention - Al Farez, Muhammad Rifky; Fachri, Helman; Ramadhan, Muhammad Ebuziyya Alif (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The Aim of this research is to identify the effect of brand image and product quality toward repurchase intention of Converse Shoes in Pontianak City with customer satisfaction as intervening variable. Method used in this research is associative. Sample used in this research are 100 persons with decided criteria such as the customers used the shoes or they had bought the Converse shoes. The data analysis technique in this research are conducted with Structural Equation Model (SEM) assisted by SmartPLS. 3.0 software. Based on the finding, the direct effect among brand image, product quality and customer satisfaction resulted positively significant toward repurchase intention. Yet, brand image did not affect customer satisfaction significantly, moreover product quality successfully affected toward customer satisfaction positive and significantly. The indirect effect of brand image intervened by customer satisfaction toward repurchase intention resulted insignificantly yet positive, lastly, the indirect effect of product quality intervened by customer satisfaction toward repurchase intention resulted positively significant. Further study is needed as the coverage of samples is limited. Converse as the corporate needs to improve the quality of their produced shoes rather than their brand image.